The Eﬃcacy and Safety of Automatic Modes During Respiratory Support After Cardiac Surgery - A. A. Yeremenko; R. D. Komnov; E. A. Koshek (Общая реаниматология, 2022)
Aims. To compare the eﬃcacy and safety of semiautonomous Adaptive Support Ventilation (ASV) and fully automated (closed-loop, Intellivent-ASV) mechanical ventilation and oxygenation versus conventional mechanical ventilation mode during respiratory support in cardiac surgery patients.Material and methods. In this study, 40 adult patients were ventilated by conventional mechanical ventilation managed by 8 physicians (control group), whereas other two groups patients were ventilated by Intellivent-ASV (n=40) or in a semiautomatic ASV mode (n=40). The groups received standard care, except for the modes of ventilation.Results. In the Intellivent-ASV group, the number of manual changes in ventilator settings was signiﬁcantly lower: 0 (0–0) versus 2 (2–3) (ASV) and 4 (3–5) in the control group (P<0.0001). There were signiﬁcant diﬀerences in the duration of respiratory support in ICU which was 226±31 min (Intellivent group) vs 259±66 (ASV) and 271±78 min (control) (P=0.0042; P1–2=0.0167; P1–3=0.009). The Intellivent-ASV group patients received more protective ventilation than patients in the semiautomated and physician-controlled groups (lower values of driving pressure (6 (6–7) cm H2O vs. 6 (6–7) and 7 (7–9) cm H2O (P<0.0001)), tidal volume (6 (6–7) vs. 7 (7–7.7) and 7 (7–8) ml/kg/PBW (P<0.0001)), FiO2 (26 (24–30)% vs. 34 (30–35)% and 34 (30–38)%) with no diﬀerences between the groups in paO2/FiO2. There were no signiﬁcant diﬀerences between the groups in frequency of undesirable events and duration of ICU stay.Conclusion. The use of intelligent technologies makes it possible to interactively individualize respiratory support, signiﬁcantly reducing clinician's involvement in this process without compromising patient safety and the quality of ventilation.